Use of eye‐pointing by children with cerebral palsy: what are we looking at?. Issue 5 (11th July 2013) - Sargent, Jenefer; Clarke, Michael; Price, Katie; Griffiths, Tom; Swettenham, John
Abstract: Background: Children with cerebral palsy often show significant communication impairment due to limited or absent speech. Further, motor impairment can restrict the use of movement, including pointing, to signal interest and intent. For some children, controlled gaze can be an effective 'point‐substitute': such 'eye‐pointing' can be used to request items, establish mutual interest in an event, or select vocabulary within an alternative or augmentative communication (ACC) system. However, in clinical practice there is a lack of clarity about how the term 'eye‐pointing' is used, how 'eye‐pointing' is recognized or how it relates to social development. Aims: To present a clinical description of the term 'eye‐pointing' with reference to children with severe cerebral palsy who cannot speak or finger‐point. To consider this description within a wider discussion of the importance of gaze in communication development. Methods & Procedures: Cumulative clinical observations during assessment of children referred to a specialist multidisciplinary communication clinic have provoked discussion between the authors on what factors precipitate use of the term 'eye‐pointing' in young children with severe cerebral palsy. In particular, discussion has centred on whether use of the term is appropriate in individual cases and whether guidance is available about how gaze should be observed in this developmentally vulnerable group of children. A literature search was also conducted in order to explore whether the use and meaning of the term is established. Conclusions & Implications: In interactions with non‐speaking children, determining whether a child is using eye‐gaze communicatively requires observation and interpretation of several factors. These processes will be informed by reflection on what is known about other aspects of the child's communication and interaction skills. Within the literature, the term 'eye‐pointing' is sometimes used when describing the communication functions of individuals using augmentative and alternative communication (AAC) systems, and is occasionally qualified by a definition. No papers have been found that set out a clinical description universally applicable to children with severe motor impairment. Moreover, guidance is lacking on how possible episodes of 'eye‐pointing' might be confidently distinguished from other episodes of directed gaze in young, developing communicators. The discussion of the term makes reference to the importance of gaze in early communication development, and explores factors that might influence gaze and its interpretation in young children with cerebral palsy. A description of eye‐pointing for this group is offered. The authors suggest that this will bring practical benefits to those supporting the communication development of children with severe cerebral palsy.